Os discursos político-jurídicos sobre o recrudescimento penal: análise da pauta da redução da maioridade penal no Congresso Nacional - Paulo, Mayara de Lima (2023)
The political-legal discourse spoken in the Brazilian Parliament can lead to profound transformations in legal practice and in various social spheres through Bills, Legislative Decrees, and Constitutional Amendments. Public (in)security is a recurring theme in Brazilian electoral campaigns, legislative debates, and mainstream media, with a portion of the population gripped by fear and insecurity. In this context, the reduction in the age of criminal responsibility is a continually renewed proposal in each legislative term, under varying conditions and scopes, achieved through amendments to the Constitutional Text, which establishes the age limit in Article 228, despite the provision of comprehensive and priority protection for children and adolescents, particularly due to the unique state of the developing person. In this socio-discursive-legal context, the problem is: what socio-discursive processes underpin the agenda of toughening juvenile criminal penalties in the Brazil’s National Congress, concerning the reduction in the age of criminal responsibility? The research uses documents such as Proposed Constitutional Amendments presented in the Federal Senate and the Chamber of Deputies, the speeches of the parliamentarians in plenary sessions and on TV. We used the qualitative and empirical theory and methodology of Critical Discourse Analysis by Fairclough. This research analyses the discourses of politicians regarding the nature of socio-educational measures, the purposes of constitutional amendments (especially imprisonment as a solution to combat violence and crime), the socio-educational system and its legal-institutional elements, the juvenile offender, and those who oppose the content of the proposal (parliamentarians and social scientists). Also compares the theoretical contribution of Thompson regarding the concept of Critical Ideology to analyze the discourse of politicians regarding juvenile offenders, the socio-educational system, and its legal-institutional elements, as well as those who oppose this constitutional amendment. Furthermore, this research uses the lessons of Foucault and his Nietzschean roots concerning the movements of domination and resistance, the concept of the orders of discourse, and the prison system and its political capital in managing illegalities. We concluded that the strategic social ignorance (Proctor) can be used as a new mode of operation for the symbolic construction of ideology (Thompson), which may demonstrate that the interest is not to contribute to the effective policies to combat violence and crime but to capitalize on social fear and outcry for popular support and political dividends in service of the State power.